The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1371/journal.pone.0099126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Host IL28B rs12979860, rs8099917 in Interferon Responsiveness and Advanced Liver Disease in Chronic Genotype 3 Hepatitis C Patients

Abstract: Background and AimsGenetic polymorphisms near interleukin 28B gene are associated with spontaneous and treatment induced clearance of hepatitis C virus (HCV). Our objective was to evaluate the impact of interleukin 28B single nucleotide polymorphism (rs12979860, rs8099917) variability in HCV genotype 3 infected populations.Methods400 hepatitis C seroreactive patients from different population groups in Eastern and North Eastern part of India were assessed for host and viral genotypic analysis. 83 HCV genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
5
9
1
Order By: Relevance
“…Consistent with earlier studies, our data have shown that polymorphisms exist in the IFNL3/IL‐28B gene in North‐Indian population. The frequency of T allele (28%) of IFNL3 (rs12979860) was found to be similar that reported in Southern‐Indian (24%) population, Caucasians (30%‐32%) population, Moroccan (32%), whereas the Oriental population carry much lower frequency (5%‐8%) of the T allele .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with earlier studies, our data have shown that polymorphisms exist in the IFNL3/IL‐28B gene in North‐Indian population. The frequency of T allele (28%) of IFNL3 (rs12979860) was found to be similar that reported in Southern‐Indian (24%) population, Caucasians (30%‐32%) population, Moroccan (32%), whereas the Oriental population carry much lower frequency (5%‐8%) of the T allele .…”
Section: Discussionsupporting
confidence: 93%
“…The frequency of T allele (28%) of IFNL3 (rs12979860) was found to be similar that reported in Southern‐Indian (24%) population, Caucasians (30%‐32%) population, Moroccan (32%), whereas the Oriental population carry much lower frequency (5%‐8%) of the T allele . Similarly, the G allele frequency (17%) of IFNL3 (rs8099917) was quite similar to that reported earlier in the Eastern‐Indian (15%) population, Caucasians (16%) population, whereas the same for IFNL3 (rs8099917) is relatively lower in Oriental (5%‐9%) population …”
Section: Discussionsupporting
confidence: 86%
“…The efficacy of PEG-INFα/RBV treatment depends, in part, on the interaction of virus and host factors [13], and SNPs may be associated with the outcome and response to treatment, specially IL28B and ITPA genotypes have been reported to be significant markers in recent trials [14,15]. For IL28B SNPs, SVR rates were higher in CC patients (54% in monoinfected patients and 67% in coinfected patients), findings similar to those reported in other studies [16][17][18]. Despite that, no significance was found, probably as a consequence of the small number of patients in both groups.…”
Section: Discussionsupporting
confidence: 84%
“…The Indian population is ethnically heterogeneous; therefore genetic variability is expected in different groups of the population. In our study population, frequencies of the favorable CC and TT genotypes at rs12979860 and rs8099917 were 53.14 and 69.84%, respectively, which is much less than that found in the study conducted by Firdaus and coworkers in chronic HCV Genotype 3 patients in the same region. It was seen in our study that the percentage of CC allele at rs12979860 was much higher (73%) in healthy individuals without thalassemia whereas our control individuals with thalassemia were found to have a low proportion of the same allele (53%) than normal controls.…”
Section: Discussioncontrasting
confidence: 78%
“…In our earlier study, we found 18.7% HCV‐seroreactive cases in the population in this region with thalassemia major . Earlier studies have shown correlation of IL28B SNPs with IFN therapy in HCV chronic patients infected with Genotype 1 in Western countries and Genotype 3 in India . However, none of the previous studies have typically focused on any particular HCV‐infected high‐risk population group.…”
Section: Discussionmentioning
confidence: 99%